Pengembangan Strategi Re-Branding UMKM Desa Majakerta untuk Meningkatkan Penjualan - Sopwan, Indra Drajat; Setiawati, Septia Eka; Muaviah, Evih; Ramadhani, Fitria; Linda, Rosih; Nurlaeli, Alisa; Wandini, Silpi; Sindiawati, Triana; Cunayah, Cunayah; Ali, Salma; Sinta, Dewi; Haekal, Muhammad; Yusuf, Maulana; Juandi, Oka Hedi; Maulana, Asep; Sopiyudin, Sopiyudin; Adilah, Moch. Yasin Nur (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Prosomi is one of the MSMEs located in Majakerta Village, Balongan District, Indramayu Regency, which processes mangoes into syrup and juice products, and there are fish ball MSMEs that use local seafood. Although these two MSMEs have significant potential, they are still not well known by the people of Indramayu Regency due to the lack of a strong visual identity and limited promotional efforts. Therefore, a strong brand identity development is necessary to attract consumer attention and increase awareness of the Mango Syrup and Fish Meatball products. The main goal of this design project is to create a stronger and more professional brand identity by designing banners, logos, and packaging that can represent the values and character of Prosomi Mango Syrup and Fish Meatballs, with the hope of strengthening the product's position in the market and enhancing its competitiveness among consumers.